Guerra in camicia nera by Berto: A Feasible Postcolonial Interpretation (ENTHYMEMA, 2024)
Postcolonial studies have known their fortune in Italy in the recent past, and publications demonstrate a fertile growth of interests and fields of investigation, accompanied by a constructive discussion of a theoretical nature.Starting from the idea that the great literary works are never an expression of the sole culture of domination - conservative and subversive at the same time - the article offers a contribution within the postcolonial critique by examining Giuseppe Berto's Guerra in camicia nera. Written by those who, at least in the first phase, openly sided with fascism, this fictionalized diary deviates from the fictional texts of propaganda to show, in formal choices, the ambiguity of meaning in relation to uniquely ideological discourses.
Keywords: Giuseppe Berto; Guerra in camicia nera; Postcolonial; Antirhetoric; Contradictions